Chloroform Fraction from Methanol Extract of Starfish Acanthaster planci Stimulates Catfish (Clarias sp.) Macrophage Immunomodulatory Activity - Janib Achmad; Ervia Yudiati; Nuril Azhar; Rabia Alghazeer (Jurnal Kelautan Tropis, 2023)
Catfish (Clarias sp.) is Indonesia's most important and popular freshwater commodity, widely cultured and intensively grown. This study is aimed to find out the effects of the chloroform fraction from a methanol extract of Acanthaster planci on non-specific immunity in Clarias sp. Thin Layer Chromatography analysis of the methanol extract's chloroform fraction yielded three fractions: FrKl3.1, FrKl3.2, and FrKl3.3. The FrKl3.3 fraction of Acanthaster planci had a significant influence on Phagocytic Activity at doses of 0.1 (54.09 ± 8.99 %), 0.3 (48.16 ± 3.34 %), 0.5 (50.39 ± 5.71 %), and 0.7 mg/kg Body Weight (46.58 ± 0.37 %). At 0.5 mg/kg Body Weight (4.03 ± 1.40 %), the Phagocytic Index of FrKl3.2 was significantly higher than the control. At 0.5 mg/kg Body Weight (38.22 ±1.43 cell 106/ml) and 0.7 mg/kg BW (40.41 ± 1.92 cell 106/ml), the number of leukocytes/white blood cells was significantly higher than the control. Nitroblue Tetrazolium and Total Plasma Protein were not significantly different from the control. Based on the results,  the FrKl3.3 was leading on phagocytic capacity and number of leukocytes